Clinical analysis of ectopic pregnancy in a tertiary center in rural Telangana - Anusha, N S Sai; Hota, Basanta Manjari; Movva, Naimisha (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To find the incidence, risk factors, morbidity and mortality in ectopic pregnancy in a tertiary center in rural Telangana. Methods: This retrospective observational study was conducted in the Department of Obstetrics and Gynecology, Mamata Medical College, Khammam, Telangana State, India, over 5 years from 2017 to 2021. Detailed informative data of all admitted and treated cases of ectopic pregnancy were collected, analyzed and discussed. Result: The incidence of ectopic pregnancy was 1.3 per 100 pregnancies and 2.5% case fatality. The majority of cases were in the 20-30 years of age group (82.5%); multipara (50%) and gestational age of ≤ 8 weeks (62.5%). History of abortion was the most common risk factor (67.5%). The classical triad of amenorrhoea, pain abdomen and bleeding per vagina was present in 45% of cases; and amenorrhea (97.5%), pain abdomen (87.5%) and vaginal bleeding (42.5%), abdominal tenderness (85%) and unstable hemodynamic (22.5%) were reported. The fallopian tube was the commonest site and operative management was required in 97.2% of cases. Conclusion: Prevention of known risk factors, early reporting and referral in need, diagnosis and effective management is the way to a better outcome in ectopic pregnancy.